Running injuries in the participants of Ljubljana marathon - Vitez, Luka (Zdravstveno varstvo, 2017)
Introduction. The aim of our study was to determine the self-reported incidence and prevalence of running-related injuries among participants of the 18 th Ljubljana Marathon, and to identify risk factors for their occurrence. Methods. A customized questionnaire was distributed over registration. Independent samples of t-test and chi- square test were used to calculate the differences in risk factors occurrence in the injured and non-injured group. Factors which appeared significantly more frequently in the injured group were included further into multiple logistic regression analysis. Results. The reported lifetime running injury (absence >2 weeks) incidence was: 46% none, 47% rarely, 4% occasionally, and 2% often. Most commonly injured body regions were: knee (30%), ankle and Achilles% tendon (24%), foot (15%), and calf (12%). Male gender, running history of 1-3 years, and history of previous injuries were risk factors for life-time running injury. In the season preceding the event, 65% of participants had not experienced any running injuries, 19% of them reported minor problems (max 2 weeks absenteeism), but 10% and 7% suffered from moderate (absence 3-4 weeks) or major (more than 4 weeks pause) injuries. BMI was identified as the solely risk factor. Conclusions. This self-reported study revealed a 53% lifetime prevalence of running-related injuries, with the predominate involvement of knee, ankle and Achilles% tendon. One out of three recreational runners experienced at least one minor running injury per season. It seems that male gender, short running experience, previous injury, and BMI do increase the probability for running-related injuries.
Keywords: dejavniki tveganja; incidence; injuries; marathons; maratoni; poškodbe; prevalenca; prevalence; risk factors; running; sport; sports; šport; tek